Macroprudential Policy Tools in Norway Strengthening Financial System Resilience - Jin, Yosuke (OECD Economics Department Working Papers, 2014)
In Norway house prices have risen to high levels, associated with very strong credit growth, in a context of low interest rates. Such a combination was in many countries a contributory factor to the 2008- 09 crisis. The Norwegian authorities have been well aware of the problem. Below-target inflation and low interest rates abroad have kept policy interest rates low. "Macro-prudential" tools have been developed as additional policy instruments with a view to strengthen the banking system's resilience to possible shocks and dampen systemic risk. This chapter notes that although authorities seem to have succeeded in containing over-heating pressures in the housing market, high levels of household indebtedness persist, a phenomenon which was an important factor in the last major Norwegian recession. The chapter also provides some longer run considerations on resource allocation in the housing market. This Working Paper relates to the 2014 OECD Economic Survey of Norway (www.oecd.org/eco/surveys/economic-survey-norway.htm)